Given the following simultaneous equations
2 x + y = 2 8
x 2 − y 3 − y 5 = 6 4
find the value of x + y where x and y are positive integers.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Sorry, the answer is x + y = 7 2 + 1 6 = 8 8 .
Log in to reply
You may edit your future solutions by clicking on the pencil at the top right of your solution. I have already edited this one for you. Btw: Great Solution!
( i ) G i v e n x & y ∈ I + ( i i ) B y i n s p e c t i o n o f b o t h e q n , 2 x & y a r e w h o l e s q u a r e n u m b e r s ( i i i ) B y 2 n d e q n x 2 = 6 4 + y 3 + y 5 / 2 ⇒ x 2 ≥ 6 4 ( a s y i s + v e ) ⇒ x ≥ 8 ( a s x i s + v e ) b y 1 s t e q n , y = 2 8 − 2 x ⇒ y ≤ 2 4 ( a s x ≥ 8 ) s o p o s s i b l e v a l u e s o f y a r e 1 , 4 , 9 , & 1 6 . U s e h i t & t r i a l ⇒ o n l y o n e s o l n ( 7 2 , 1 6 ) x + y = 7 2 + 1 6 = 8 8
Nicely done Sir
Problem Loading...
Note Loading...
Set Loading...
From the first equation 2 x + y = 2 8 , we note that for 2 x to be an integer, 2 x = 2 × 2 n 2 ) and x = 2 n 2 , where n = 1 , 2 , 3 . . . , 1 3 .
Substitute into the first equation:
4 n 2 + y = 2 8 ⇒ y = 2 8 − 2 n , this means that y is even and y ≤ 2 6 .
From the second equation x 2 − y 3 − y 5 = 6 4 , we note that y have to be an integer and since y is even, y = 4 m 2 and y = 4 m 2 , where m = 1 , 2 , . . . . Since y ≤ 2 6 , y = 4 or 1 6 .
From the second equation, when y = 4 ,
x 2 − 4 3 − 4 5 = 6 4
⇒ x 2 = 6 4 + 6 4 + 3 2 = 1 6 0 ⇒ x = 4 1 0 which is not an integer.
When y = 1 6 ,
⇒ x 2 = 6 4 + 1 6 3 + 1 6 5 = 6 4 + 4 0 9 6 + 1 0 2 4 = 5 1 8 4
⇒ x = 5 1 8 4 = 7 2
∴ x + y = 7 2 + 1 6 = 8 8